Inclusive design in architectural practice: Experiential learning of disability in architectural education. Issue 2 (April 2018) - Mulligan, Kerry; Calder, Allyson; Mulligan, Hilda
Abstract: Background: The built environment can facilitate or impede an individual's ability to participate in society. This is particularly so for people with disability. Architects are well placed to be advocates for design that enhances societal equality. Objective: This qualitative study explored architectural design students' perceptions of inclusive design, their reflections resulting from an experiential learning module and the subsequent influence of these on their design practice. Methods: Twenty four architectural design students participated in focus groups or individual interviews. Data were analyzed thematically. Results: Three themes were evident: 1) Inclusive design was perceived as challenging, 2) Appreciation for the opportunity to learn about the perspectives of people with disabilities, and 3) Change of attitude toward inclusive design. Experiential learning had fostered reflection, changes in attitude and the realization that inclusive design, should begin at the start of the design process. Conclusions: For equitable access for all people to become reality, experiential learning, coupled with positive examples of inclusive design should be embedded in architectural education.